RECONSTRUCTING LAST GLACIAL MAXIMUM BOTTOM WATER SALINITIES FROM DEEP-SEA SEDIMENT PORE FLUID PROFILES - Adkins J.F.; Schrag D.P. (My University, 2003)
Deep-sea sediment pore fluids contain a record of past glaciations in their [Cl] and δ18O. The signal of the Last Glacial Maximum (LGM) ice volume increase remains in the pore fluids as a local peak in each of these species. Using a one-dimensional model to account for the diffusive and advective transport within the sediment column since the LGM, the past bottom water salinity and δ18Oseawater values can be estimated. The model is most sensitive to the shape of the forcing function used to represent bottom water variations through time, the effective diffusion coefficient, and the scatter in the data. Assuming steady-state compaction, the model is relatively insensitive to the initial condition, the bulk sedimentation rate and the assumed porosity profile, though these last two are measured independently. Overall uncertainties in the relative [Cl] increase at the LGM are between 0.1 and 0.5%, where the mean ocean change is about 3.5%.
Keywords: PALEOSALINITY; DIFFUSION; LAST GLACIAL MAXIMUM